Quality characteristics of cookies made with red rice flour composite flour - Leong Kar Yee; Syaidahtull Naseha Ibrahim; Macdalyna Esther Ronie; Ahmad Hazim Abdul Aziz; Rovina Kobun; Wolyna Pindi; Jumardi Roslan; Norazlina Md Ridhwan; Nicky Rahmana Putra; Hasmadi Mamat (Researchgate, 2024)
Red rice flour (RRF) is renowned for its nutritional richness, particularly in terms of total dietary fiber and essential minerals. This flour is derived from red rice, a variety of rice known for its distinctive red husk and bran layer. The study aimed to identify the best formulation through sensory evaluation, determine nutritional composition, physical characteristics, and assess shelf life compared to a control cookie. Five formulations of red rice cookies were prepared with RRF substitution levels ranging from 20% to 100%. The F2 red rice cookie with 40% RRF substitution was chosen as the best formulation based on sensory evaluation. It showed similarities to the control cookie in terms of sensory attributes. Nutritional analysis revealed lower moisture and crude protein content but higher crude fiber and total dietary fiber in the F2 compared to the control. Physical analysis showed lower hardness and different color characteristics for the F2. Consumer study results indicated high acceptability for the F2 red rice cookie. In conclusion, this study offers a promising strategy to improve the nutritional profile of cookies by boosting their dietary fiber content, effectively addressing a common deficiency observed in cookies made with conventional wheat flour